Relationship Between Menarch Age and Dysmenorrhea Pain in Female Students - Sherkia Prakasiwi; Fitriani Nur Damayanti (Universitas Muhammadiyah Semarang, 2023)
Dysmenorrhea can cause disruption of several activities such as lower academic achievement, inhibit sleep performance and quality, have a negative impact on mood, and cause anxiety and depression. Several studies state that dysmenorrhea can interfere with daily activities. approximately 10-15% of women are absent from school and lost time at work caused by dysmenorrhea. This study aims to determine the relationship between menarche and the incidence of dysmenorrhea in female students at Al-Mabrur Islamic Boarding School. This research is quantitative research, using primary data (questionnaire). The research method uses a cross-sectional method with the aim of knowing the relationship between the independent variables and the dependent variable. Data was collected using a questionnaire and analyzed using the chi-square test. The number of samples was 91 female students who had experienced menstruation, the samples were obtained using the total sampling technique. The result of the calculation of the Pearson chi-square statistical test is 20.883 while the chi-square table is 5.991. This means that the calculated chi-squared value is greater than the table chi-squared value. The p-value is 0.000 while the significant level is 0.05. This means that the p-value is smaller than the significant level. The conclusion is that there is a relationship between the age of menarche and dysmenorrhea.Dismenore dapat menyebabkan terganggunya beberapa aktivitas seperti menurunkan prestasi akademik, menghambat kinerja dan kualitas tidur, berdampak negatif pada suasana hati, serta menimbulkan kecemasan dan depresi. Beberapa penelitian menyatakan bahwa dismenore dapat mengganggu aktivitas sehari-hari. sekitar 10-15% wanita tidak masuk sekolah dan kehilangan waktu kerja yang disebabkan oleh dismenore. Penelitian ini bertujuan untuk mengetahui hubungan antara menarche dengan kejadian dysmenorrhea pada santri putri di Pesantren Al-Mabrur. Penelitian ini merupakan penelitian kuantitatif, dengan menggunakan data primer (kuesioner). Metode penelitian menggunakan metode cross-sectional dengan tujuan untuk mengetahui hubungan antara variabel bebas dan variabel terikat. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis dengan menggunakan uji chi-square. Jumlah sampel sebanyak 91 siswi yang telah mengalami menstruasi, sampel diperoleh dengan menggunakan teknik total sampling. Hasil perhitungan uji statistik chi square Pearson adalah 20,883 sedangkan chi square tabel adalah 5,991. Artinya nilai chi kuadrat hitung lebih besar dari nilai chi kuadrat tabel. Nilai p adalah 0,000 sedangkan tingkat signifikan adalah 0,05. Artinya p-value lebih kecil dari taraf signifikan. Kesimpulannya adalah ada hubungan antara usia menarche dengan dismenore.